Proyectación y contexto sociocultural : El desarrollo de competencias asociadas - Marincoff, Gustavo (2017)
The aim of Cultural Integration I, a subject of the courses Industrial Design and Visual Communication Design of the Facultad de Bellas Artes of the Universidad Nacional de La Plata, is to provide the future professional designer with useful tools to analyze their task in the society of knowledge. Through its Workshop Area, conceptual tools are provided from the social sciences to analyze the socio-cultural context of the project processes and to develop the professional skills required to correctly define the problem that the project must solve.